Phytochemical Profile, Antioxidant, Anti-Atopic, and Anti-Inflammatory Activities of Filipendula glaberrima Nakai at Different Growth Stages - Hak-Dong Lee; Genevieve Tonog; Neil Patrick Uy; Yunji Lee; Ki-Young Kim; Hangeun Kim; Sanghyun Lee (MDPI AG, 2024)
Since atopic dermatitis is an inflammatory skin disease, natural remedies, such as Filipendula glaberrima Nakai (FG), with anti-inflammatory properties are possible promising therapeutic options. This study aimed to investigate the therapeutic potential of FG extracts at different growth stages. Seven compounds were isolated from the FG leaf extracts using open-column chromatography, and they were analyzed using HPLC. The extracts were further evaluated for their total polyphenol and flavonoid content (TPC and TFC). The in vitro antioxidant properties of the FG extracts were evaluated using radical scavenging assays, whereas their anti-inflammatory activities were assessed by evaluating their ability to inhibit the production of inflammation-associated biomarkers using the Griess assay and ELISA, respectively. The MTT assay was used to evaluate the viability and cytotoxicity of the FG extracts in keratinocyte cell lines. The results showed that the full-flowering stage exhibited the highest TPC, TFC, and antioxidant activities, thus suggesting a positive correlation between these properties. All FG extracts showed significant anti-inflammatory activity by inhibiting the production of pro-inflammatory biomarkers in lipopolysaccharide-stimulated macrophages. Additionally, the FG extracts suppressed the production of cytokines and chemokines in keratinocytes, indicating their anti-atopic potential. HPLC analysis revealed that the full-flowering stage had the highest content of all the analyzed phytochemicals (gallic acid, (+)-catechin, hyperin, miquelianin, astragalin, afzelin, and quercetin). These results suggest that the full-flowering stage of FG is the most promising source for therapeutic applications owing to its superior phytochemical profile and biological activities. This study highlights the potential of FG extracts, particularly in its full-flowering stage, as a natural therapeutic agent for the management of inflammation-related diseases, and it can also serve as a reference for further research on FG.